Validation of the EcoEvol fuel catalyst remediation and refining efect and its effect on improving performance in internal combustion engines - Lazo-Hoyos, Darío Eder (2016)
Internal combustion engines are widely use in several economical activities such as transport, power generation, mining, etc. Fossil fuels, especially gasoline and diesel, are a crucial input for their operation. A little known factor that affects its performance is their microbiological contamination. In this regard, the EcoEvol C fuel catalyst was engineered to solve this problem, promoting better operating conditions for internal combustion engines, generating reductions in polluting exhaust emissions, fuel savings and power improvement.